Spirolones A–E, five spiroketals from a productive saline soil derived Penicillium raistrickii - Liu, Desheng; Ma, Liying; Rong, Xianguo; Kang, Huihui; Liu, Weizhong (Frontiers in Microbiology, 2024)
BackgroundIn recent decades, spiroketals which features with two rings joined by a spiro atom, have stimulated a great deal of researches for their diverse significant biological activities. Fungi are proved to be key reservoirs of structurally unique chemical skeletons. Up to date, [6,6]-spiroketals from fungal strains are still sporadically reported. Guided by UV information based on HPLC-DAD system, five unreported azaphilone-based [6,6]-spiroketals (1-5), named spirolones A-E, along with one known analogue, pestafolide A (6), were isolated from a productive saline soil derived fungus Penicillium raistrickii.MethodsTheir planar structures were solved through a comprehensive set of spectroscopic techniques including UV, IR, HRESIMS and 1D/2D NMR. The absolute configurations were determined by X-ray single-crystal diffractions or the modified Mosher’s method. The misassignment of absolute configuration of pestafolide A was revised by X-ray crystallographic analysis in this study. All the isolated compounds were screened for antibacterial effect against Pseudomonas aeruginosa, Staphylococcus aureus and Escherichia coli based on the microplate approach and the cytotoxicity towards HepG2 and Hep3B cell lines based on MTT assay.Results and discussionThe results suggested that compound 4 displayed some activity against P. aeruginosa and E. coli with MIC values of 35.00 μg/mL and 55.00 μg/mL, with MIC values of the positive control of streptomycin at 12.50 μg/mL and 8.00 μg/mL, respectively. Compound 5 exhibited inhibitory effect against HepG2 cell line with IC50 value of 3.40 μM, and 8.14 μM against Hep3B cell line with doxorubincin as positive control. Compounds 4 and 5 may be capable of contribution for the development of new antibiotics or antitumor agents.